O padre médico de Grajaú: a trajetória de Frei Alberto Beretta no sertão maranhense (1949 a 1981) - Dias, Paula Regina Pereira dos Santos Marques (Universidade do Vale do Rio dos Sinos, 2023)
This thesis, titled “The Doctor Priest of Grajaú: The trajectory of Friar Alberto Beretta in the Maranhão bowels (1949 to 1981)”, aims to investigate the performance of this Italian doctor and priest in healthcare area in the Maranhão bowels. The study of the life trajectory of Friar Alberto Beretta, who arrived in the city of Grajaú (MA) in 1949, place that he chose to provide care to the poorest community, allows us to discuss his performance and contributions in the area of health, relegated by the public entities, due to the insufficiency of doctors to take treatments to the countryside of Maranhão state, even the simplest ones. The issues that involve this life trajectory, especially regarding Friar Alberto’s medical performance, consists the main object of this work. Considering this, firstly it was sought in this work to address the arrival of Friar Alberto in Brazil, as well as to observe his motivations for choosing this place, reconstituting Brazil as a country of Italian Capuchin missions, and his arrival in the city of Grajaú (MA), prelature administered by the Italian Capuchin order since its creation in 1922. The thesis also presents the difficulties and achievements of Friar Alberto Beretta in the construction of Saint Francis of Assisi Hospital, the first hospital in the region, a work completed in 1964; his revalidation process of the Medicine Course in Porto Alegre, Rio Grande do Sul, and also proposes an analysis of his performance as a doctor in the care of local communities, especially leprosy patients and the poor population, emphasizing the use of techniques considered experimental, especially in the 1960s and 1970s. Aspects linked to regional and local contexts were also contemplated throughout the work. Regarding to the theoretical and methodological aspects, this research dialogues with the History of Health, Social History and life trajectory analysis. The sources analyzed were the files of the Diocese of Grajaú and the Convent of Carmo Caput et Mater of the Congregation in São Luís (MA), containing letters, newspapers, testimonial reports, three biographical books, as well as personal files provided by the guardian of the Virgínia Beretta family documents. The research reveals a character with a leading role in medical practice in the bowels region of Maranhão, in the 30 years of his stay in the city of Grajaú, providing health care services of great relevance.
Keywords: Frei Alberto Beretta; Trajetória; História da saúde; Sertão maranhense; Grajaú; Trajectory; Health history; Maranhão bowels; ACCNPQ::Ciências Humanas::História